Lidocaine iontophoresis in myofascial pain syndrome: A controlled study - Kaya, A; Kamanli, A; Ozgocmen, S; Bayik, Y; Ardicoglu, O (B M J Publishing Group, 2003)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 18, 2003 -- LISBON, PORTUGAL